2011
DOI: 10.1073/pnas.1018593108
|View full text |Cite
|
Sign up to set email alerts
|

An actin cytoskeleton with evolutionarily conserved functions in the absence of canonical actin-binding proteins

Abstract: Giardia intestinalis, a human intestinal parasite and member of what is perhaps the earliest-diverging eukaryotic lineage, contains the most divergent eukaryotic actin identified to date and is the first eukaryote known to lack all canonical actin-binding proteins (ABPs). We sought to investigate the properties and functions of the actin cytoskeleton in Giardia to determine whether Giardia actin (giActin) has reduced or conserved roles in core cellular processes. In vitro polymerization of giActin produced fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
166
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(173 citation statements)
references
References 51 publications
5
166
2
Order By: Relevance
“…In most eukaryotes, actin is highly conserved and its function and dynamics are impacted by a standard set of actin binding proteins. Interestingly, the intestinal parasite Giardia intestinalis contains one of the most divergent eukaryotic actins and also lacks many of the canonical actin binding proteins (44). This fascinating "exception to the rule" supports a hypothesis that preservation of essential interactions between actin and its conserved regulatory partners is a key evolutionary constraint that limits the protein's sequence divergence among eukaryotes.…”
Section: Discussionmentioning
confidence: 67%
“…In most eukaryotes, actin is highly conserved and its function and dynamics are impacted by a standard set of actin binding proteins. Interestingly, the intestinal parasite Giardia intestinalis contains one of the most divergent eukaryotic actins and also lacks many of the canonical actin binding proteins (44). This fascinating "exception to the rule" supports a hypothesis that preservation of essential interactions between actin and its conserved regulatory partners is a key evolutionary constraint that limits the protein's sequence divergence among eukaryotes.…”
Section: Discussionmentioning
confidence: 67%
“…That giActin performs similar functions to actin in other eukaryotes suggests these processes were already associated with actin at the time Giardia split from the other eukaryotes (13). We have also shown that giRac, the sole Rho family GTPase in Giardia, regulates actin despite the absence of all actin-binding proteins known to link G-protein signaling to the actin cytoskeleton (Arp2/3, formin, wave, myosin, and cofilin) (13). Therefore, Giardia must contain a novel set of actin-interacting proteins comprised of ancient yet undiscovered and/or Giardia-specific actin regulators.…”
mentioning
confidence: 99%
“…Their absence may indicate a split from the last eukaryotic common ancestor before the canonical set of actin-binding proteins was established. Alternatively, Giardia may have evolved a novel set of actin-interacting proteins that allowed for the gradual loss of the canonical set of actin-binding proteins (11,13). Our previous work has shown that despite the lack of canonical actinbinding proteins, Giardia actin (giActin) is required for conserved cellular functions, including membrane trafficking, cytokinesis, polarity, and control of cellular morphology (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At 24 hours after transfection cells were harvested and either lysed and analyzed by western blotting or fixed for immunofluorescence. For western blots, cells were harvested, lysed in Laemmli SDS sample buffer, resolved on a 10% acrylamide gel that was then transferred to a non-fluorescent PVDF membrane and probed using anti-HA (HA-7, Sigma, 1:3000), anti-MPM2 (MPM2, Millipore, 1:1000) or anti-actin (Paredez et al, 2011) (1:3000), followed by fluorescent secondary antibody (IRDye680-linked anti-mouse and IRDye800-linked anti-rabbit, Li-Cor). Signals were detected and quantified using the Odissey infrared imager.…”
Section: Cyclin B Assays In Giardiamentioning
confidence: 99%